Maximally improper interference in underlay cognitive radio networks - Lameiro, Christian; Santamaría, I.; Utschick, W.; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Measurement-driven quality assessment of nonlinear systems by exponential replacement - Stein, Manuel; Nossek, Josef A.; Barbé, Kurt (Proc.\ IEEE Int. Instrum. & Meas. Tech.\ Conf.)

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11 n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (Proc. IEEE International Conference on Communications (ICC))

An integrated 118.4 to122 GHz low noise phase-locked loop (PLL) in 0.13 µm SiGe BiCMOS technology - Ali, U.; Bober, M.; Thiede, Andreas (2016 German Microwave Conference (GeMiC))

Shaped Gaussian Dictionaries for Quantized Networked Control Systems with Correlated Dropouts - Peters, E. G. W.; Quevedo, D. E.; stergaard, J. (Trans. Signal Processing)

Maximum Hands-Off Control: A Paradigm of Control Effort Minimization - Nagahara, M.; Quevedo, D. E.; Nešić, D. (Trans. Automat. Contr.)

Multiple Descriptions for Packetized Predictive Control - stergaard, J.; Quevedo, D. E. (EURASIP J. Adv. Signal Processing)

Controller and scheduler codesign for feedback control over IEEE 802.15.4 networks - Peters, E. G. W.; Quevedo, D. E.; Fu, M. (Trans. Contr. Syst. Technol.)

Discrete-time hands-off control by sparse optimization - Nagahara, M.; stergaard, J.; Quevedo, D. E. (EURASIP J. Adv. Signal Processing)

Robust stability of a class of Networked Control Systems - Lješnjanin, M.; Nešić, D.; Quevedo, D. E. (Automatica)

Kalman Filtering With Relays Over Wireless Fading Channels - Leong, A. S.; Quevedo, D. E. (Trans. Automat. Contr.)

Characterization of maximum hands-off control - Chatterjee, D.; Nagahara, M.; Quevedo, D. E.; Rao, K. S. M. (Syst. & Contr. Lett.)

On Network Topology Reconfiguration for Remote State Estimation - Leong, A. S.; Quevedo, D. E.; Ahlén, A.; Johansson, K. H. (Trans. Automat. Contr.)

Event Driven Modeling and Characterization of the Second Order Voltage Switched Charge Pump PLL - Ali, Ehsan; Hangmann, Christian; Hedayat, Christian; Haddad, Fayrouz; Rahajandraibe, Wenceslas; Hilleringmann, Ulrich (IEEE Transactions on Circuits and Systems I: Regular Papers)
Keywords: Electrical and Electronic Engineering

Influence of Traps on the Characteristics of ZnO Nanoparticles Thin-Film Transistors - Vidor, Fabio F.; Meyers, Thorsten; Wirth, Gilson I.; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

Self-aligning integration technique for organic electronics - Meyers, Thorsten; Vidor, Fabio F.; Kaijage, Shubi F.; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

Low-voltage DNTT-based thin-film transistors and inverters for flexible electronics - Meyers, Thorsten; Vidor, Fábio F.; Brassat, Katharina; Lindner, Jörg K.N.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Microstructured Metal Layers in Dye Sensitized Solar Cells - Kleine, Andre; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

ZnO nanoparticle thin-film transistors on flexible substrate using spray-coating technique - Vidor, Fábio F.; Meyers, Thorsten; Wirth, Gilson I.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Inverter Circuits Using ZnO Nanoparticle Based Thin-Film Transistors for Flexible Electronic Applications - Vidor, Fábio; Meyers, Thorsten; Hilleringmann, Ulrich (Nanomaterials)
Keywords: General Materials Science; General Chemical Engineering

Organic Field-Effect and Nanoparticle Thin-Film Transistors: Static Model - Romero, Adrian; Gonzalez, Jesus; Hilleringmann, Ulrich; Gloesekoetter, Peter (ANALOG 2016; 15. ITG/GMM-Symposium)

Influence of UV irradiation and humidity on a low-cost ZnO nanoparticle TFT for flexible electronics - Vidor, F. F.; Meyers, T.; Hilleringmann, Ulrich; Wirth, G. I. (2015 IEEE 15th International Conference on Nanotechnology (IEEE-NANO))

Improved rf design using precise 3d near-field measurements and near-field to far-field transformations - Hangmann, C; Mager, T; Khan, S; Hedayat, C; Hilleringmann, Ulrich (Smart System Integration-International Conference and Exhibition on Integration Issues of Miniaturized Systems)

High-Q whispering gallery microdisk resonators based on silicon oxynitride - Hett, T.; Krämmer, S.; Hilleringmann, Ulrich; Kalt, H.; Zrenner, A. (Journal of Luminescence)
Keywords: Condensed Matter Physics; Biochemistry; General Chemistry; Atomic and Molecular Physics; and Optics; Biophysics

Erweiterung des Raman-Nath-Modells zur Analyse von Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (Technisches Messen)

Lehrerbildung im Mechatronik Studium an der Hochschule Hamm-Lippstadt - Jonas-Ahrend, Gabriela; Thikomirov, Dmitri (Digitale Vernetzung der Facharbeit)

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Investigations into Bluetooth Low Energy Localization Precision Limits - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (24th European Signal Processing Conference (EUSIPCO 2016))
In this paper we study the influence of directional radio patterns of Bluetooth low energy (BLE) beacons on smartphone localization accuracy and beacon network planning. A two-dimensional model of the power emission characteristic is derived from measurements of the radiation pattern of BLE beacons carried out in an RF chamber. The Cramer-Rao lower bound (CRLB) for position estimation is then derived for this directional power emission model. With this lower bound on the RMS positioning error the coverage of different beacon network configurations can be evaluated. For near-optimal network planing an evolutionary optimization algorithm for finding the best beacon placement is presented.

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (2016 IEEE International Conference on Communications (ICC))

Planar prism spectrometer based on adiabatically connected waveguiding slabs - Civitci, F.; Hammer, Manfred; Hoekstra, H.J.W.M. (Optics Communications)
The device principle of a prism-based on-chip spectrometer for TE polarization is introduced. The spectrometer exploits the modal dispersion in planar waveguides in a layout with slab regions having two different thicknesses of the guiding layer. The set-up uses parabolic mirrors, for the collimation of light of the input waveguide and focusing of the light to the receiver waveguides, which relies on total internal reflection at the interface between two such regions. These regions are connected adiabatically to prevent unwanted mode conversion and loss at the edges of the prism. The structure can be fabricated with two wet etching steps. The paper presents basic theory and a general approach for device optimization. The latter is illustrated with a numerical example assuming SiON technology.
Keywords: tet_topic_waveguide

Full Resonant Transmission of Semiguided Planar Waves Through Slab Waveguide Steps at Oblique Incidence - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Journal of Lightwave Technology)
Sheets of slab waveguides with sharp corners are investigated. By means of rigorous numerical experiments, we look at oblique incidence of semi-guided plane waves. Radiation losses vanish beyond a certain critical angle of incidence. One can thus realize lossless propagation through 90-degree corner configurations, where the remaining guided waves are still subject to pronounced reflection and polarization conversion. A system of two corners can be viewed as a structure akin to a Fabry-Perot-interferometer. By adjusting the distance between the two partial reflectors, here the 90-degree corners, one identifies step-like configurations that transmit the semi-guided plane waves without radiation losses, and virtually without reflections. Simulations of semi-guided beams with in-plane wide Gaussian profiles show that the effect survives in a true 3-D framework.
Keywords: tet_topic_waveguide

Unveiling Nanometer Scale Extinction and Scattering Phenomena through Combined Electron Energy Loss Spectroscopy and Cathodoluminescence Measurements - Losquin, Arthur; Zagonel, Luiz F.; Myroshnychenko, Viktor; Rodríguez-González, Benito; Tencé, Marcel; Scarabelli, Leonardo; Förstner, Jens; Liz-Marzán, Luis M.; García de Abajo, F. Javier; Stéphan, Odile; Kociak, Mathieu (Nano Letters)
Plasmon modes of the exact same individual gold nanoprisms are investigated through combined nanometer-resolved electron energy-loss spectroscopy (EELS) and cathodoluminescence (CL) measurements. We show that CL only probes the radiative modes, in contrast to EELS, which additionally reveals dark modes. The combination of both techniques on the same particles thus provides complementary information and also demonstrates that although the radiative modes give rise to very similar spatial distributions when probed by EELS or CL, their resonant energies appear to be different. We trace this phenomenon back to plasmon dissipation, which affects in different ways the plasmon signatures probed by these techniques. Our experiments are in agreement with electromagnetic numerical simulations and can be further interpreted within the framework of a quasistatic analytical model. We therefore demonstrate that CL and EELS are closely related to optical scattering and extinction, respectively, with the addition of nanometer spatial resolution.
Keywords: tet_topic_plasmonics

How planar optical waves can be made to climb dielectric steps - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Optics Letters)
We show how to optically connect guiding layers at different elevations in a 3-D integrated photonic circuit. Transfer of optical power carried by planar, semi-guided waves is possible without reflections or radiation losses, and over large vertical distances. This functionality is realized through simple step-like folds of high-contrast dielectric slab waveguides, in combination with oblique wave incidence, and fulfilling a resonance condition. Radiation losses vanish, and polarization conversion is suppressed for TE wave incidence beyond certain critical angles. This can be understood by fundamental arguments resting on a version of Snell’s law. The two 90° corners of a step act as identical partial reflectors in a Fabry–Perot-like resonator setup. By selecting the step height, i.e., the distance between the reflectors, one realizes resonant states with full transmission. Rigorous quasi-analytical simulations for typical silicon/silica parameters demonstrate the functioning. Combinations of several step junctions can lead to other types of optical on-chip connects, e.g., U-turn- or bridge-like configurations.
Keywords: tet_topic_waveguide

Subwavelength binary plasmonic solitons - Kou, Yao; Förstner, Jens (Optics Letters)
We study the formation of subwavelength solitons in binary metal-dielectric lattices. We show that the transverse modulation of the lattice constant breaks the fundamental plasmonic band and suppresses the discrete diffraction of surface plasmon waves. New types of plasmonic solitons are found, and their characteristics are analyzed. We also demonstrate the existence of photonic-plasmonic vector solitons and elucidate their propagation properties.
Keywords: tet_topic_polariton

Robust Population Inversion by Polarization Selective Pulsed Excitation - Mantei, D.; Förstner, Jens; Gordon, S.; Leier, Y. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Scientific Reports)
The coherent state preparation and control of single quantum systems is an important prerequisite for the implementation of functional quantum devices. Prominent examples for such systems are semiconductor quantum dots, which exhibit a fine structure split single exciton state and a V-type three level structure, given by a common ground state and two distinguishable and separately excitable transitions. In this work we introduce a novel concept for the preparation of a robust inversion by the sequential excitation in a V-type system via distinguishable paths.
Keywords: tet_topic_qd

Interference of surface plasmons and Smith-Purcell emission probed by angle-resolved cathodoluminescence spectroscopy - Yamamoto, Naoki; Javier García de Abajo, F.; Myroshnychenko, Viktor (Physical Review B)
We investigate the interplay between geometrical lattice resonances and surface plasmons mediating the emission of Smith-Purcell visible light via angle-resolved cathodoluminescence spectroscopy. We observe strong modulations in the dispersion curves of Smith-Purcell radiation (SPR) when they intersect the surface plasmons of silver gratings using a 200-kV transmission electron microscope. The decay of the plasmons away from the grating is directly probed by controlling the electron-beam position relative to the sample surface with nanometer precision. Our measurements are in excellent agreement with numerical simulations, clearly revealing the presence of characteristic Fano profiles resulting from the interference of the light continuum and the discrete plasmon states for each direction of emission. The intensity anomaly in the SPR emission pattern can be well explained from the geometrical consideration of the intersections between the dispersion planes of the SPR and surface plasmon polariton (SPP). A strong and directional SPR beam can be realized under the condition that the SPR dispersion plane comes in contact with the band edge of the SPP dispersion plane.

Detection of ultrasonic plate waves using ceramic strip transducers - Claes, Leander; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Proceedings SENSOR 2015)
Keywords: piezoceramics; strip transducers; plate waveguide; dispersion diagram

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Effective large-scale PV integration: Methods to match load profile with actual PV output - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources and the use of hydro power for fluctuation compensation in Cameroon - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Cost, performance, and yield comparison of eight different micro-inverters - Krauter, Stefan; Bendfeld, Jörg (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

BOS cost reduction via direct PV charging of electrical vehicles - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Stabilizing oﬀshore wind farm power feed-in via power to gas storage systems - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Discovering the potential for oﬀshore windfarms trough measurements - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Wind power forecasting for oﬀshore wind farms - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)